2007
DOI: 10.1128/cvi.00188-07
|View full text |Cite
|
Sign up to set email alerts
|

Use of Saccharomyces cerevisiae -Expressed Recombinant Nucleocapsid Protein To Detect Hantaan Virus-Specific Immunoglobulin G (IgG) and IgM in Oral Fluid

Abstract: Hantaan virus (HTNV) is the prototype species of the genus Hantavirus and has remained the epidemiologically most important species in the genus until now. Hantaviruses form a separate genus within the family Bunyaviridae, forming a group of closely related negative-stranded RNA viruses (4,17,25,29). Hantaviruses are the causative agents of hemorrhagic fever with renal syndrome (HFRS) and hantavirus pulmonary syndrome. HFRS occurs mainly in Europe and Asia and is associated with HTNV, Seoul virus (SEOV), Dobra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…In line with data obtained for yeast-expressed HTNV antigen [83,84], we found a very similar sensitivity and specificity of the PUUV-Bawa antigen-based indirect ELISA (99 and 100%) and mAb-capture ELISA (95 and 100%) for the serum panel from Germany. A comparison of the results of the validation of the indirect PUUV-Vra ELISA and the PUUV-Bawa mAb-capture ELISA for all investigated sera from Finland showed a lower sensitivity for the capture ELISA (89%) than for the indirect ELISA (100%), but a higher specificity (100 and 95%, respectively).…”
Section: Reactivity Of Human Sera and Mabs With Different Puuv N Antisupporting
confidence: 89%
“…In line with data obtained for yeast-expressed HTNV antigen [83,84], we found a very similar sensitivity and specificity of the PUUV-Bawa antigen-based indirect ELISA (99 and 100%) and mAb-capture ELISA (95 and 100%) for the serum panel from Germany. A comparison of the results of the validation of the indirect PUUV-Vra ELISA and the PUUV-Bawa mAb-capture ELISA for all investigated sera from Finland showed a lower sensitivity for the capture ELISA (89%) than for the indirect ELISA (100%), but a higher specificity (100 and 95%, respectively).…”
Section: Reactivity Of Human Sera and Mabs With Different Puuv N Antisupporting
confidence: 89%
“…The reactivity of yeast-expressed SBV N protein with SBV IgG-positive cow sera is in line with previous studies that demonstrated the usefulness of recombinant viral N proteins expressed in different heterologous systems for serological diagnosis of bunyaviruses infection both by western blot and ELISA [1721]. The N protein of bunyaviruses is the most abundant viral antigen present in the virion and in the infected cells, thus making it an excellent target for serology as well as epidemiological studies of viral infections [1618].…”
Section: Resultssupporting
confidence: 87%
“…The N protein of bunyaviruses is the most abundant viral antigen present in the virion and in the infected cells, thus making it an excellent target for serology as well as epidemiological studies of viral infections [ 16 18 ]. Recombinant N protein of hantaviruses, generated in E. coli , insect cells, or yeast, has been widely used for detection of hantavirus-specific antibodies in human sera and oral fluid [ 17 21 ]. SBV N protein was expressed recently in E. coli [ 11 , 32 ] and used for the development of a commercial diagnostic kit for serologic diagnosis of SBV infection [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…[23,24,29,30] and indirect ELISAs for SNV, PUUV, HTNV and ANDV using E. coliexpressed N antigens [8,21,34]. The seroepidemiological study in four counties of two administrative districts of Lower Bavaria revealed an overall prevalence of 6.7% with a range of 0% in Schöfweg (district Freyung-Grafenau), 4.1% in Geiersthal (district Regen), 5.9% in Kirchberg (district Regen) and 11.9% in Spiegelau (district Freyung-Grafenau).…”
Section: Discussionmentioning
confidence: 98%